Acceptance of e-services among public employees: an empirical investigation from the Palestinian public sector. (1st September 2020) - Al-Habil, Wasim; Aboramadan, Mohammed; Fares, Mohammed
This study aims to uniquely investigate the factors associated e-services acceptance in the Palestinian public sector. Our study is based on the framework of the technology acceptance model (TAM2). 612 questionnaires were collected from the employees of the Palestinian ministry of education and were valid for statistical analysis using SmartPLS. The study findings show that there exist positive relationships between prior experience, job relevance, output quality, result demonstrability and perceived ease of use and positive relationships between image, job relevance, output quality and result demonstrability and perceived usefulness. The findings also revealed that there are significant positive relationships between perceived ease of use and perceived usefulness with users' intention to use. Our results give evidence that TAM2 holds in the Palestinian context and provides useful recommendation including managerial intervention for better organisational e-services in the public sector. The study is one of the few studies that investigate the adoption of e-services in a non-western context.